Regulation of expression of human RNA polymerase II-transcribed snRNA genes - Guiro, J; Murphy, S (Royal Society, 2017)
In addition to protein-coding genes, RNA polymerase II (pol II) transcribes numerous genes for non-coding RNAs, including the small-nuclear (sn)RNA genes. snRNAs are an important class of non-coding RNAs, several of which are involved in pre-mRNA splicing. The molecular mechanisms underlying expression of human pol II-transcribed snRNA genes are less well characterized than for protein-coding genes and there are important differences in expression of these two gene types. Here, we review the DNA features and proteins required for efficient transcription of snRNA genes and co-transcriptional 3' end formation of the transcripts.